Glycemic control in patients with diabetes mellitus and cardiovascular disease monitored at a reference outpatient clinic - Becker, Alexandre Dalpiaz; de Lima, Eliandra; Ledur, Priscila dos Santos; Schaan, Beatriz D`Agord (Clinical and Biomedical Research, 2014)
Introduction: Controlling hyperglycemia in diabetes mellitus is an important part of the treatment and is associated with long-term reduction of chronic complications. However, it is difficult to achieve, and different approaches to glycemic control are being investigated. We aimed to analyze glycemic control in a sample of patients treated at a tertiary hospital, as well as to analyze possible predictors of good glycemic control during follow-up. Methods: In this observational study, we collected data from the electronic medical records of patients with type 2 diabetes treated at a reference outpatient clinic. We analyzed demographic, clinical and laboratory variables (blood glucose, glycosylated hemoglobin (HbA1c), lipids, creatinine and microalbuminuria). Results: Out of 57 patients, 61.4% (n = 35) had HbA1c levels ≤ 8% (controlled diabetes mellitus group, CDM), and 38.6% (n = 22) did not reach this value (uncontrolled diabetes mellitus group, UDM) in 1 year. Most patients in the UDM group were women (p = 0.030). Age, association with other comorbidities, educational attainment, and duration of diabetes were not different between groups. The number of scheduled appointments was similar between groups, but the number of attended appointments was higher in the UDM group. Initial glycemic control was worse in the UDM group (HbA1c 9.2 ± 1.4 vs. 11.0 ± 1.5%, p < 0.001). Outpatient discharge was more frequent in the CDM group (p = 0.01). Conclusion: Intensifying diabetes care by a specialized team at tertiary centers can improve metabolic control for the majority of these patients, especially for those with a lower HbA1c at the time of referral.